Observing the performance of distribution systems with embedded generators - Ciric, R. M.; Padilha-Feltrin, A.; Denis, IFED (Wiley-Blackwell, 2004)
In this paper, a multi-objective approach for observing the performance of distribution systems with embedded generators in the steady state, based on heuristic and power system analysis, is proposed. The proposed hybrid performance index describes the quality of the operating state in each considered distribution network configuration. In order to represent the system state, the loss allocation in the distribution systems, based on the Z-bus loss allocation method and compensation-based power flow algorithm, is determined. Also, an investigation of the impact of the integration of embedded generators on the overall performance of the distribution systems in the steady state, is performed. Results obtained from several case studies are presented and discussed. Copyright (C) 2004 John Wiley Sons, Ltd.
Keywords: distribution networks; dispersed generators; distribution management system; performance indices